(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the author will try to consider the possible causes of difficulties in teaching the discipline of academic writing to Uzbek students. The article will consider the topic of the existence of the discipline of academic writing in the higher school curriculum. The purpose of the work is to find a solution to the problematic issues of teaching this discipline, which, according to the reviews of colleagues reflected in publications, have already accumulated a lot. As a way out of the problematic situation, the author suggests dividing the discipline into three levels, each of which covers a number of educational competencies necessary to create a certain result within the genre of academic text.